COMPARATIVE ANALYSIS OF THE EVALUATION OF UNIVERSITY COOPERATION WITH THE SOCIO-ECONOMIC ENVIRONMENT ON THE EXAMPLE OF THE REPUBLIC OF POLAND AND THE FEDERAL REPUBLIC OF GERMANY - Kuliński, Mateusz Wojciech (Torun International Studies, 2023)
Purpose: The purpose of this scientific article is to conduct a comparative analysis of the evaluation of university cooperation with the socio-economic environment, using the examples of the Republic of Poland and the Federal Republic of Germany, and to identify the differences between the analysed systems as a determining factor for the superiority of the German higher education system over the Polish system. Methodology: Three research methods were employed to achieve the chosen research objective: the formal-dogmatic method (dogmatic-legal), the comparative law method (legal comparativism), and the empirical method (empirical research) as an auxiliary method. The formal-dogmatic method was used to analyse the logical and linguistic regulations governing the institutional framework of agencies responsible for the quality of education in Poland and Germany. The comparative law method will be implemented through classical comparative legal research aimed at analysing the similarities and differences in legal regulations regarding the evaluation of university cooperation with the socio-economic environment in the Republic of Poland and the Federal Republic of Germany. The empirical method was used as an auxiliary method to analyse the thesis presented by the author, which is the superiority of German universities over Polish universities. Findings: The article points out fundamental differences in the legal status of agencies responsible for the quality of education and the systems of quality evaluation in the area of university cooperation with the socio-economic environment in the Republic of Poland and the Federal Republic of Germany. Furthermore, the author identifies this state of affairs as one of the factors determining the superiority of the German higher education system over the Polish system. Originality/value: The chosen research objective represents an unexplored field so far. There is a lack of studies in the domestic and European markets that aim to systematically compare the evaluation of university cooperation with the socio-economic environment in the Republic of Poland and the Federal Republic of Germany. The conducted analysis and the resulting conclusions effectively fill this gap.